1967
DOI: 10.1126/science.157.3790.829
|View full text |Cite
|
Sign up to set email alerts
|

Blood Viscosity: Influence of Erythrocyte Aggregation

Abstract: The addition of purified canine or bovine fibrinogen to suspensions of canine erythocytes in Ringer solution caused an increase in viscosity and the formation of aggregates of erythocytes. Both of these effects became increasingly pronounced as the fibrinogen concentration was raised, and they approached plateaus with 1 gram of fibrinogen per 100 milliliters. An increase in shear rate (or shear stress) reduced both the effect on viscosity and the aggregate size. The data suggest that fibrinogen causes an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(131 citation statements)
references
References 8 publications
5
126
0
Order By: Relevance
“…Valant et al 30 have reported the viscosity curves obtained for three female and three male healthy donors at 37 C with different hematocrit (Hct) values. For all donors, the viscosity was markedly shear-thinning confirming the early measurements of Chien et al 46,47 and Thurston 4 and providing evidence of contributions of both viscosity and elasticity in the rheology of whole blood (which will be separately evaluated as G 0 and G 00 afterwards). At low shear rates, the red blood cells tend to aggregate leading to a solid-like behavior, but as the shear rate is increased the red blood cells disaggregate and align with the flow imparting a liquid-like behavior to blood, with a reduced ability to store elastic energy.…”
Section: A Viscoelastic Properties Of Bloodsupporting
confidence: 62%
“…Valant et al 30 have reported the viscosity curves obtained for three female and three male healthy donors at 37 C with different hematocrit (Hct) values. For all donors, the viscosity was markedly shear-thinning confirming the early measurements of Chien et al 46,47 and Thurston 4 and providing evidence of contributions of both viscosity and elasticity in the rheology of whole blood (which will be separately evaluated as G 0 and G 00 afterwards). At low shear rates, the red blood cells tend to aggregate leading to a solid-like behavior, but as the shear rate is increased the red blood cells disaggregate and align with the flow imparting a liquid-like behavior to blood, with a reduced ability to store elastic energy.…”
Section: A Viscoelastic Properties Of Bloodsupporting
confidence: 62%
“…Furthermore, human red blood cells were found [15] not to cohere in physiological saline solution free of macromolecules such as fibrinogens. Although this may be due to electrostatic repulsion, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Age, smoking, fibrinogen, total serum proteins, and triglycerides were adjusted covariates. Lipoprotein variables were successively introduced in the multivariate models: apoA-I and apoB (model 1); LDL-C, HDL 2 …”
Section: Discussionmentioning
confidence: 99%